The Effect of Students’ Learning Independence and Cognitive Learning Style on Atomic Physics PEFI4421 Learning Achievement - *, Prayekti; Rasyid, Rasyimah (IJRDO- Journal of Educational Research, 2017)
In this study, the researcher explored the contributions of independence in learning and cognitive learning style towards students’ learning achievement on Atomic Physics course PEFI4421 in semester 1, 2017 academic year. This study employed a double linear regression analysis. The analysis measured influences of a free variable on a bound variable. The measurement of this influence included one free variable (X) and one bound variable (Y), called the simple linear regression analysis with the following formula Y = a+bX. In this study, this formula was used for measuring the contribution of two free variables on one bound variable. Sample of this study were the students that already passed the Atomic Physics course in Open University Indonesia under 2016 (2 semesters) and 2017 (1 semester) academic year with an underlying assumption that the students were homogenous since they all had completed the course in a considerably recent time period. The results of this study showed that (1) not all of the students of Physics Education had the learning materials of Atomic Physics; (2) the students who dominantly had a field independent cognitive learning style and learning independence achieved maximum learning achievements of Atomic Physics; and (3) the students’ graduation year did not determine the influence of the cognitive learning style and learning independence since their graduation years were still considered to be recent.